Video pembelajaran ramah disabilitas bagi komunitas e- sports ability Indonesia - Charlie Tjokrodinata; Cendera Rizky Anugrah Bangun; Helga Liliani Cakra Dewi; Dian Nuranindya; Riatun (Jurnal Komunikasi Profesional, 2022)
E-Sports Ability Indonesia (EAI / IG @ebility.id) is an esports community that is equalized for people with disabilities. The community, which was founded in 2019, has managed to get 123 members. One of the goals of establishing EAI is to become a shelter for people with disabilities so that they can develop their interests and talents in the field of esports. The lack of friendly job providers for the disabled makes it difficult for them to find work outside of community activities. In addition, the knowledge of people with disabilities on how to apply for a job or make a good CV is still very minimal. Especially during the current COVID-19 pandemic, companies are forced to reduce the number of employees and even close to reduce operational costs. One alternative that can be done by people with disabilities in the midst of the current limitations is to sell online through e-commerce. In addition to not requiring a physical store presence, selling online can also be learned easily. For this reason, this Community Service activity is intended to provide training materials to facilitate the process of finding or applying for jobs in the form of disability-friendly videos. So that people with disabilities can easily follow and understand the training materials presented. It is hoped that users of this video will gain practical knowledge about how to apply for a job and how to increase income by selling online through e-commerce.